Late-Stage C–H Arylation of Azepinoindole via Pd/Cu Catalysis: A Step Efficient and Convergent Synthesis of Rucaparib - Beckers, Igor; O’Rourke, Galahad; De Vos, Dirk (Synthesis, 2021)
The C–H arylation of indoles holds the promise to shorten synthetic routes in the production of pharmaceuticals. However, late-stage C–H activation reactions often rely on the presence of protecting groups or stoichiometric metal additives. The regiospecific C–H arylation of a highly functionalized azepino[5,3,4-cd]indole scaffold lacking directing groups via Pd(II) and Cu(II) co-catalysis is reported. The direct C–H coupling was demonstrated in the convergent synthesis of rucaparib, an FDA approved anticancer drug.
Keywords: C–H activation; indole; arylation; homogeneous catalysis; palladium; copper; organic synthesis; pharmaceuticals